Effect of UV activation on acid and catalytic properties of zeolite-containing catalysts in conversion of gas-condensate straight-run gasolines to high-octane gasolines; Russian Journal of Applied Chemistry; Vol. 84, iss. 10 - Erofeev V. I. Vladimir Ivanovich; Medvedev A. S.; Koval’ L. M.; Khomyakov I. S. Ivan Sergeevich; Erofeev M. V. Mikhail Vladimirovich; Tarasenko V. F. Victor Fedotovich (Organic synthesis and industrial organic chemistry, 2011)
Title screen